Committee of Public Security and its role in the French Revolution (1793 – 1794) - Aaeed, Israa shershab (Thi Qar Arts Journal, 2025)
The formation of the Committee of Public Safety was a pivotal event in the history of the French Revolution due to its significance and influential role in shaping the course of events. Several internal and external factors contributed to its establishment. Among the most prominent was the execution of King Louis XVI in early 1793, which alarmed the monarchs of Europe who feared a similar fate. This led to the creation of an international coalition against France in 1793, comprising England, Prussia, Russia, Portugal, Austria, Sardinia, Spain, and the Netherlands, placing France in a precarious external position.The situation was further exacerbated by internal uprisings in various French provinces and a severe economic crisis sweeping the country. In response to these challenges, the National Convention established the Committee of Public Safety on April 16, 1793. Initially composed of nine members, the number later increased to twelve. The committee was granted broad powers that enabled it to suppress internal unrest and confront external military threats. It even shifted the military balance in favor of France, moving from a defensive stance to offensive operations, and regained control over all French territories and surrounding areas.However, internal conflicts soon emerged within the committee due to policy disagreements, especially as the justification for the Reign of Terror began to wane. Some members called for a policy of mercy and moderation, which provoked the ire of the committee’s leader, Robespierre. He eliminated his opponents and issued the Law of 22 Prairial (June 10, 1794), which abolished parliamentary immunity. This act was not forgiven by the members of the National Convention, who orchestrated a coup against him and executed him on July 28, 1794.The following day, July 29, the committee’s membership was renewed, its powers were reduced, and its authority was limited to military and diplomatic affairs. Its absolute powers were revoked, and a system was introduced to renew one-quarter of its members monthly, with re-election prohibited. This marked the restoration of the National Convention’s authority and control over the country.